High incidence of venous thromboembolism but not of coronary artery disease in granulomatosis with polyangiitis in first years after diagnosis - Borowiec, Anna; Hadzik-Blaszczyk, Malgorzata; Kowalik, Ilona; Rusinowicz, Tomasz; Krupa, Renata; Kandyba, Piotr; Jozefik, Ewa; Gawalkiewicz, Anna; Jankowski, Jan; Zycinska, Katarzyna (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2019)
Objectives: Granulomatosis with polyangiitis (GPA), previously known as Wegener’s granulomatosis, is one of antineutrophil cytoplasmic autoantibody (ANCA) – associated vasculitis. In patients with GPA an increased incidence of venous thromboembolism (VTE), mainly during active disease, has been described. The aim of the present study was to assess the incidence of VTE and its relation with classic risk factors for atherosclerosis, presence of coronary artery disease (CAD), echocardiographic parameters and laboratory findings in GPA patients. Methods: The group of consecutive patients with GPA were followed in the study. In all patients echocardiography and laboratory tests were performed. Results: Ninety six patients with GPA were followed for mean 3 years. In 16 patients (16.6%) VTEs occurred in association with GPA, of which 56% occurred 6 months before or one year after diagnosis of GPA. Classic risk factors for atherosclerosis were present in 77 patients (80.2%) at some moment during follow-up. In patients with VTE there were larger right ventricle diameter (p=0.041) and higher right ventricle systolic pressure (p=0.022) observed. VTEs occurred significantly less frequently in patients treated with cyclophosphamide (p=0.049). In this study group VTE occurred more frequently than CAD: 16 (16.7%) vs. 4 (4.2%); p=0,0049. Patients with VTE were younger than those with CAD (p=0.053) and had higher levels of ANCA-PR 3 (p=0.016). Conclusions: Patients with granulomatosis with polyangiitis in first years after diagnosis have higher risk of venous thromboembolism than coronary artery disease. This finding is probably related to hypercoagulability induced by the disease and its therapy.